Deleterious phenotypes in wild Arabidopsis arenosa populations are common and linked to runs of homozygosity - Barragan, A Cristina; Collenberg, Maximilian; Schwab, Rebecca; Kersten, Sonja; Kerstens, Merijn H L; Požárová, Doubravka; Bezrukov, Ilja; Bemm, Felix; Kolár, Filip; Weigel, Detlef (G3 (Bethesda, Md.), 2024)
In this study, we aimed to systematically assess the frequency at which potentially deleterious phenotypes appear in natural populations of the outcrossing model plant Arabidopsis arenosa, and to establish their underlying genetics. For this purpose, we collected seeds from wild A. arenosa populations and screened over 2,500 plants for unusual phenotypes in the greenhouse. We repeatedly found plants with obvious phenotypic defects, such as small stature and necrotic or chlorotic leaves, among first-generation progeny of wild A. arenosa plants. Such abnormal plants were present in about 10% of maternal sibships, with multiple plants with similar phenotypes in each of these sibships, pointing to a genetic basis of the observed defects. A combination of transcriptome profiling, linkage mapping and genome-wide runs of homozygosity patterns using a newly assembled reference genome indicated a range of underlying genetic architectures associated with phenotypic abnormalities. This included evidence for homozygosity of certain genomic regions, consistent with alleles that are identical by descent being responsible for these defects. Our observations suggest that deleterious alleles with different genetic architectures are segregating at appreciable frequencies in wild A. arenosa populations.
Keywords: semena rostlinná; Arabidopsis arenosa; wild populations; fenotyp; Chromosome Mapping; Phenotype; abnormal phenotypes; reference genome; runs of homozygosity; mapování chromozomů; Arabidopsis; Seeds